The role of mesoscopic structuring on the intermixing of spin-polarised conduction channels in thin-film ferromagnets for spintronics. (21st August 2017) - Alcer, D; Atkinson, D
Abstract: The separation of spin-up and spin-down conduction channels is fundamental to electronic transport in ferromagnets and essential for spintronic functionality. The spin states available for conduction are defined by the ferromagnetic material, but additional physical factors can affect scattering and modify the spin-dependence of conduction. Here the effect of mesoscopic structuring, arising during the growth of ferromagnetic thin films, on the electronic transport was investigated. Resistivity and anisotropic magnetoresistance were measured in a series of Ni80 Fe20 thin films as a function of nominal film thickness from 3 nm up to 20 nm . The observed thickness dependence of the resisivity and magnetic anisotropy of resistivity are interpreted using a model that accounts for the macroscopic structuring from the growth of the films and incorporates a structural dependence of the spin-flip scattering. The model shows good agreement for both the thickness dependence of the resistivity and the reduction of the anisotropic magnetoresistivity. The latter indicating that increasing mixing of the conducting spin channels occurs in ultra-thin films, mainly a consequence of macroscopic structuring of the films.